Negotiating an international master franchise agreement - Mendelsohn, Martin...[et al] (Sweet & Maxwell LondonGB, 2002)
Tracks the course of a negotiation from the proposal by the franchisor; the response by the prospective master franchisee followed by a reply with some concession.